Chitosan oligosaccharides suppress LPS-induced IL-8 expression in human umbilical vein endothelial cells through blockade of p38 and Akt protein kinases - Liu Hong-tao; Huang Pei; Ma Pan; Liu Qi-shun; Yu Chao; Du Yu-guang (Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether and how COS inhibited IL-8 production in LPS-induced human umbilical vein endothelial cells (HUVECs). Methods: RT-PCR, enzyme-linked immunosorbent assays (ELISA) and Western blotting were used to study IL-8 expression and related signaling pathway. Wound healing migration assays and monocytic cell adhesion analysis were used to explore the chemotactic and adhesive activities of HUVECs. Results: COS 50–200 μg/mL exerted a significant inhibitory effect on LPS 100 ng/mL-induced IL-8 expression in HUVECs at both the transcriptional and translational levels. In addition, COS 50–200 μg/mL inhibited LPS-induced HUVEC migration and U937 monocyte adhesion to HUVECs in a concentration-dependent manner. Signal transduction studies suggest that COS blocked LPS-induced activation of nuclear factor-κB (NF-κB) and activator protein-1 (AP-1) as well as phosphorylation of p38 mitogen-activated protein kinase (MAPK) and phosphokinase Akt. Further, the over-expression of LPS-induced IL-8 mRNA in HUVECs was suppressed by a p38 MAPK inhibitor (SB203580, 25 μmol/L) or a phosphatidylinositol 3-kinase (PI3K) inhibitor (LY294002, 50 μmol/L). Conclusion: COS inhibited LPS-induced IL-8 expression in HUVECs through the blockade of the p38 MAPK and PI3K/Akt signaling pathways.